MENGOPTIMALKAN KONSEP MADRASAH DAN PESANTREN BERLANDASAN FALSAFAH PENDIDIKAN ISLAM - Aulan Nuriyah; Johan Rafaro; Nur Azmil Azizah; M. Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Madrasahs and Islamic boarding schools are two models of Islamic education that have developed in Indonesia, each with their own characteristics and strengths. Madrasahs integrate religious and general education, while Islamic boarding schools place greater emphasis on in-depth religious teaching with a boarding school pattern and the tradition of the kyai as the center of education. Although both have great potential in educating a generation that is faithful and knowledgeable, separate management and non-synergistic curricula result in less than optimal educational outcomes. This study uses a qualitative descriptive method to describe the existing conditions without manipulating the data, thereby producing a true understanding. This study discusses how to optimize the concepts of madrasahs and Islamic boarding schools through the integration of management and curriculum based on the philosophy of Islamic education, which prioritizes a balance between religious and general knowledge. The results of the study show that the synergy between madrasahs and Islamic boarding schools can strengthen the quality of Islamic education rooted in the Qur'an and Sunnah and the integral value of tawhid, thereby producing a generation with character, knowledge, and readiness to face the challenges of the times.